CULTIVATION OF MEDICINAL PLANTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article provides data on the cultivation of medicinal plants, on the law of the President on the cultivation of medicinal plants on an industrial scale. On measures to expand the scale of scientific research on the cultivation and processing of medicinal plants, the development of the establishment of their seed production.